Inhibition of microparticle release triggers endothelial cell apoptosis and detachment - Abid Hussein, Mohammed N.; Böing, Anita N.; Sturk, Augueste; Hau, Chi M.; Nieuwland, Rienk (Thrombosis and Haemostasis, 2007)
Endothelial cell cultures contain caspase 3-containing microparticles (EMP), which are reported to form during or after cell detachment. We hypothesize that also adherent endothelial cells release EMP, thus protecting these cells from caspase 3 accumulation, detachment and apoptosis. Human umbilical vein endothelial cells (HUVEC) were incubated with and without inhibitors of microparticle release (Y-27632,calpeptin), both in the absence or presence of additional “external stress”, i.e. the apoptotic agent staurosporin (200 nM) or the activating cytokine interleukin (IL)-1α (5 ng/ml). Control cultures contained mainly viable adherent cells and minor fractions of apoptotic detached cells and microparticles in the absence of inhibitors. In the presence of inhibitors, caspase 3 accumulated in adherent cells and detachment tended to increase. During incubation with either staurosporin or IL-1α in the absence of inhibitors of microparticle release, adherent cells remained viable, and detachment and EMP release increased slightly. In the presence of inhibitors, dramatic changes occurred in staurosporin-treated cultures. Caspase 3 accumulated in adherent cells and >90% of the cells detached within 48 hours. In IL-1α-treated cultures no accumulation of caspase 3 was observed in adherent cells, although detachment increased. Scanning electron microscopy studies confirmed the presence of EMP on both adherent and detached cells. Prolonged culture of detached cells indicated a rapid EMP formation as well as some EMP formation at longer culture periods. Inhibition of EMP release causes accumulation of caspase 3 and promotes cell detachment, although the extent depends on the kind of “external stress”. Thus, the release of caspase 3-containing microparticles may contribute to endothelial cell survival.
Keywords: Apoptosis; microparticles; endothelial cells